Improving Story Writing Skills through Jigsaw Cooperative Learning in Indonesian Language Classes - Putri Khairatun; Syahru Ramadhan; Syarifuddin Syarifuddin (Journal of Islamic Education Students (JIES), 2026)
This study aims to examines the implementation of the Jigsaw-type cooperative learning model in Indonesian language learning through active learning strategies to improve the story writing skills of fifth-grade students at MIS Nurul Ilmi, Bima City. The novelty of this research lies in the integration of the Jigsaw cooperative learning model with active learning strategies to strengthen students’ participation and creativity in story writing activities in elementary classrooms. This research employed a qualitative approach involving one Indonesian language teacher and 23 fifth-grade students selected based on their participation in the learning process. Data were collected through classroom observations, interviews, and documentation. The data analysis was conducted using qualitative procedures, including data reduction, coding, categorization, and interpretation, while data validity was strengthened through source and technique triangulation. The findings show that the implementation of the Jigsaw cooperative learning model combined with active learning strategies creates an interactive and collaborative learning environment. Students become more active in discussing ideas, organizing story structures, and expressing their creativity in writing. Consequently, this learning approach contributes to improving students’ story writing skills and learning engagement in Indonesian language classes.